INDIA’S BEAUTY AND STRENGTH LIES IN ITS UNITY IN DIVERSITY - Ahmad Shairgojri, Aadil; Ahmad Mir, Ishfaq (International Journal of Social Science, Educational, Economics, Agriculture Research and Technology (IJSET), 2022)
There are many distinct faiths, castes, dialects, and ways of life in India. However, there is always a sense of oneness in the midst of our differences. The same spirit of togetherness that led to our freedom is essential to our nation's continued growth and well-being. We can only grow into great nations if there is peace. People of various classes, sects, and religions have coexisted peacefully in India for centuries. To make matters worse, they've been cohabiting for decades. This clearly demonstrates the Indian people's extraordinary tolerance and cohesion. The country is a fantastic example of the concept of unity in diversity. The world's oldest civilization is found in India. We have been ruled by a variety of people from different religions and cultures over the course of 5000 years. In addition, a large number of individuals immigrated to India, which welcomed them with open arms. This interaction has allowed us to see a wide range of religious, cultural, racial, and religious diversity in our country. But despite the country's many differences, the Indian people persevered through the darkest hours and dealt with every crisis with a united spirit. "Unity among difference" is the thread that links all Indians together. There are a number of different sorts of diversity in India, as well as a wide range of definitions of "diversity," which we'll cover below. In India, there are a variety of civilizations, religions, languages, and customs that may be traced from Jammu to Kanyakumari. However, India's concept of unity in variety is characterized by people coming together in love and harmony, despite their differences.